Control of cardiovascular risk factors and health behaviors in patients post acute coronary syndromes eligible for protein convertase subtilisin/kexin-9 inhibitors. (15th January 2020) - Butty, Audrey; Gencer, Baris; Koskinas, Konstantinos C.; Carballo, David; Räber, Lorenz; Klingenberg, Roland; Matter, Christian M.; Lüscher, Thomas F.; Windecker, Stephan; Muller, Olivier; Rodondi, Nicolas; Mach, François; et al.
Abstract: Background: We aimed to examine cardiovascular risk factors and health behaviors in patients with acute coronary syndromes (ACS) according to potential extension of eligibility criteria for protein convertase subtilisin/kexin-9 inhibitors (PCSK9i) to all patients with low-density lipoprotein cholesterol (LDL-c) equal or above 1.8 mmol/l. Methods: In this prospective cross-sectional study, patients with ACS between 2009 and 2016 and with available LDL-c at one year were considered. We defined three mutually exclusive groups of patients according to eligibility for PCSK9i: "not eligible", "currently eligible", and "newly eligible". We explored the control of cardiovascular risk factors and health behaviors. Results: Out of 3025 patients who had an ACS one year ago, 1071 (35.4%) were not eligible for PCSK9i, 415 (13.7%) were currently eligible, and 1539 (50.9%) were newly eligible. The proportion of patients with uncontrolled hypertension in the not eligible group was lower than in the group currently eligible (27.6% vs 33.6%, p = 0.02), but similar to the group newly eligible (27.6% vs 28.2%, p = 0.73). The proportion of smokers in the not eligible group was lower than in the group currently eligible (21.2% vs 28.0%, p = 0.02), but similar to the group newly eligible (21.2% vs 22.5%, p = 0.51). Conclusions: More than half of patients with ACS would be additionally eligible for PCSK9i if prescription is extended from current guidelines to all patients with LDL-c equal or above 1.8 mmol/l. Patients currently eligible for PCSK9i one year after an ACS had a worst control of cardiovascular risk factors than patients potentially newly eligible. Highlights: More than half of acute coronary syndrome patients were newly eligible for PCSK9i. Newly and not eligible patients: similar control of cardiovascular risk factors. Patients newly eligible had a better health profile than those currently eligible.